Volcanic ash hazards to aviation - Prata, Alfredo; Rose, William I. (Digital Commons @ Michigan Tech, 2015)
Volcanic ash is a significant hazard to aviation, causing engine failure, damage to avionics systems and abrasion to exposed airframe parts. In this Chapter we describe the hazards, impacts, quantification and the regulatory environment associated with the ash/aviation problem. Significant developments have happened since the recent European-wide aviation shutdown due to volcanic ash from the Eyjafjallajökull (Iceland) eruption in April and May 2010. Improvements in detection from satellite, airborne and ground-based instruments, in dispersion modelling and forecasting and greater engagement between the industry, academia and regulatory bodies have all led to greater awareness and understanding. Here we provide the background to these improvements and give a summary of the various techniques used to observe and quantify ash from satellites, whilst stressing the importance of forecasting and modelling the dispersion of ash in the atmosphere. Changes in the regulatory environment, the introduction of concentration limits and safety cases are also discussed.